Metabolic regulation of Ganoderma lucidum extracts in high sugar and fat diet-induced obese mice by regulating the gut-brain axis. (February 2020) - Diling, Chen; Yinrui, Guo; Longkai, Qi; Xiaocui, Tang; Yadi, Liu; Jiaxin, Feng; Xiangxiang, Zhu; Miao, Zeng; Ou, Shuai; Dongdong, Wang; Yizhen, Xie; Yang, Burton B.; et al.
Graphical abstract: Highlights: A high sugar and fat diet affects multiple systems and organs. Alcohol extracts of the G. lucidum fruit body can improve the microbiome-gut-liver axis. Alcohol extracts of the G. lucidum fruit body can improve the microbiome-gut-brain axis. Alcohol extracts of the G. lucidum fruit body can regulate the CNS and improve metabolic regulation. Abstract: In this study, an obese mouse model was developed by administering a high sugar and fat diet for 60 days, followed by administration of a special dietary supplement of Ganoderma lucidum extract for another 35 days. Then, the changes in histopathology of the liver, adipose, colon, intestines, spleen, renal and brain tissues; metabolism and transcription; and gut microbiota were monitored. The results showed that alcohol extracts of the G. lucidum fruit body could reduce body weight; change the serum levels of lipid; ameliorate the damage to the gut microbiota, colon, liver, brain and other organs induced by the high sugar and fat diet; and activate the leptin regulatory pathways in the hypothalamus to improve metabolism. These findings indicate that administration of the alcohol extracts of the G. lucidum fruit body has beneficial effects on the microbiome-gut-liver and microbiome-gut-brain axes, and activates leptin-mediated signaling to improve metabolic regulation.